Thirty something & the clock is ticking what happens when you can no longer ignore the baby question - Edwards, Kasey (Ebury Press, 2011)
"When Kasey Edwards discovers she'll be infertile within a year, she is forced to bring the baby issue to the forefront of her mind. In "30-Something and the Clock Is Ticking", she explores what having a child would mean to her identity, her career, her body, her relationships and her mental health. Kasey speaks to people who have children and people who don't, women who claim motherhood is the best thing they've ever done and those who say it's the worst. She discovers how the desire for a baby can drive people to the brink of insanity, the logistical challenges of ovulating and trying to conceive on a longhaul flight, the indignity and despair of IVF and the price of buying sperm on the Internet. This witty memoir will make you laugh, cry and ponder the joys and regrets of motherhood. It will inspire you to tackle the baby issue head-on and on your own terms, rather than letting time, denial and social pressures make the decision for you."--Publisher's description.